Percakapan Pastoral Yesus Dengan Simon Petrus : Analisis Naratif Yohanes 21:15-19 Dan Implikkasinya Bagi Percakapan Pastoral Pelayan Gereja Yang Hendak Mengundurkan Diri - Ade Efra Anugrah (SCRIPTA: Jurnal Teologi dan Pelayanan Kontekstual, 2023)
The Bible gives the reader a narrative in John 21:15-19 about the Lord Jesus having a pastoral conversation with Simon Peter who was about to resign and return to his old profession.  Through this text, the author wants to raise and explore it using qualitative methods with a narrative approach from Mark Allan Powell. Through narrative criticism, the author sees events in three important elements where there are events, characters, and places that are in the narrative and draws them out by placing themselves as writers and shadow readers.  This study seeks to answer the question of what Jesus, the Master, through the pastoral conversation, was in the view of the narrator so that Simon Peter gave up his intention to resign from the ministry and what are the implications for the minister of the church who wanted to resign because the leader left ? .  The results of the study found that the Pastoral conversation of the Lord Jesus to Simon Peter evoked cognitive aspects, affection aspects, and psychomotor aspects. The opposition to these aspects can be used by the leader who is about to leave the place of service where there is his servant who intends to resign and follow him.